ANALISIS DAMPAK RASIO KEUANGAN PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERCATAT PADA JII - Astuti Astuti; Elly Susanti; Hery Pandapotan Silitonga (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The research method uses qualitative data, secondary data sources, using documentation methods, classic data assumption test analysis techniques, coefficient of determination, hypothesis testing. The object of research in companies incorporated in the Jakarta Islamic Index in the period 2014 - 2018. The results of this study by F statistical tests show that all independent variables influence the dependent variable. In statistical test t current ratio has a negative and significant effect on stock prices. Size and Debt to Asset Ratio influence and are not significant on stock prices. Return on Assets has a positive and significant effect on stock prices.